Escape from Original Home: Do Metastatic Cells Stay Dormant or Destructive? - Aye Aye Wynn; Nang Khin Mya; Tin Tin Thein (Penerbit UMS, 2024)
Metastasis is defined as tumour implants discontinuous with the primary tumour. It is responsible for most cancer-related mortality. Many factors relating to the tumour and host factors are involved in the presence of metastasis and the long-term prognosis of the disease process. This study observed available literature and aims to emphasise tumours and their interaction with the tumour microenvironment. Epigenetic and genetic influences on pathogenesis, tumour and microenvironment interaction, role of epithelial-mesenchymal transition in metastasis are essential determinants of advanced malignant diseases. Early detection of metastatic disease is an essential part. The histopathological aggressiveness of a tumour and its biological behaviour determine the probability of metastasis and advanced disease. Understanding these factors has a benefit to improving the current therapies and diagnostic approaches to an advanced level, leading to the prevention of metastasis and more successful management of patients.